Bioethanol production from cassava and sugar cane molasses - Iderus, Nadia Natasha; Mohd Shaha, Nurhaslinda; Mohameda, Elizah; Mohd Kassima, Angzzas Sari; Abdul Hamid, Mariani (Penerbit UTHM, 2022)
Bioethanol is produced from the fermentation of sugar. The process required sugar to produce ethanol derived from fuel or energy crops such as cassava, molasses, and sugar cane. Basically, ethanol is burned to produce carbon dioxide and water, releasing energy. The advantages of bioethanol over the conventional gasoline are higher volumetric energy density, higher engine compression ratios and cheaper price of gasoline produced. This study compares the production of bioethanol from cassava and molasses in terms of its retail prices, ease of accessible resources, global warming potential and dependence on fossil fuels. Besides, the effects of bioethanol production also were discussed in the related topic of food security, feedstock supply security, job opportunities, improvement of air quality, impact on deforestation, fuel price stability and stabilizing the income of farmers.